Manajemen Perencanaan Program Festival Jazirah Arab untuk Mengembangkan Bahasa dan Seni Arab - Al Lastu Nurul Fatim; Ahmad Faizal Amin; Tsabit Nurrahman; Zakiyah Arifa (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
This study describes the model of approach, scope, and planning process of the Arabian Peninsula Festival (FJA) program to develop Arabic language and art learning. This research uses the descriptive qualitative method. The Data collection used is the method of interview, observation, and documentation. The results of this study are: first, the FJA program uses a bottom-up planning approach model, which overall program planning starts from the proposal or idea of some BSA HMJ management members and lecturers as compilers of the objectives of developing Arabic language and art learning. Second, the scope of this program includes short-term activities that are held regularly once a year and are incidental on a national scale. Third, the planning process has been carried out optimally with a preparation time of two months, then the stages of the activity procedure are clear and easily understood by the participants, namely the assistance of activity guidelines that determine the race by reflecting the development of Arabic language and arts such as speech, singing, poetry, calligraphy, debates, essays, reading news, and MQK in Arabic.